2003
DOI: 10.1177/00223433030405003
|View full text |Cite
|
Sign up to set email alerts
|

Defense Pacts and International Trade

Abstract: Theories of international political influences on trade maintain that shared alliance commitments affect bilateral commercial exchange. The most prominent of these suggests that trade produces a security externality threatening states, but that a military alliance alleviates these concerns, leading to greater trade among allies. Yet past empirical analyses produce inconsistent findings with respect to the effect of military alliances on bilateral trade levels. This article presents a new argument to explain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 40 publications
10
68
0
1
Order By: Relevance
“…He argues that "when designing empirical analyses, researchers include a much broader range of security agreements in the category of military alliance than necessary to capture the concept in their argument." 141 Long arrives at the same conclusion as we did in our hypothesis; among the different types of alliances-defense pact, neutrality and non-aggression pact, and entente-only the defense pacts meet the required indicators for a military alliance. "Namely those classified as defense pacts, obligate the members to provide military assistance to a partner in the event of an attack upon the partner's sovereignty and/or territorial integrity."…”
Section: E Trade Exchangesupporting
confidence: 69%
See 1 more Smart Citation
“…He argues that "when designing empirical analyses, researchers include a much broader range of security agreements in the category of military alliance than necessary to capture the concept in their argument." 141 Long arrives at the same conclusion as we did in our hypothesis; among the different types of alliances-defense pact, neutrality and non-aggression pact, and entente-only the defense pacts meet the required indicators for a military alliance. "Namely those classified as defense pacts, obligate the members to provide military assistance to a partner in the event of an attack upon the partner's sovereignty and/or territorial integrity."…”
Section: E Trade Exchangesupporting
confidence: 69%
“…142 Thus, after narrowing down the model, Long finds statistical evidence that "defense pacts [between major powers from 1885 to 1990] are positively related to dyadic trade levels, and that their nondefense-pact counterparts are not significantly related to trade in a dyad." 143 Another possible explanation for the varying results of the alliance and trade relationship is dedicated to Long and Leeds, who argue that another factor is also complementary to the relationship between alliance formation and increased trade. They find empirical evidence that additional promises of economic cooperation prompt allies to trade more with each other than with states that have no economic ties to the allies.…”
Section: E Trade Exchangementioning
confidence: 99%
“…This suggests that allied states have an incentive to trade more with allies than with non-allies because trade between allies can enhance the security of the alliance. Long (2003) found that variations in the type of alliance agreements explained the alliance-trade relationship. He found that defense pacts promote trade between allies, while other types of alliances did not.…”
Section: The Korean Journal Of International Studies 14-2 212mentioning
confidence: 99%
“…Several scholars have argued, for example, that alliances lead to increased trade among members, both because government trade policies favor allies and because firms seek business ties with states that they believe are less likely to engage in conflict with their home state; this relationship has been particularly evident since World War II (e.g., Gowa & Mansfield, 1993;Long, 2003). Similarly, Li and Vashchilko (2010) find that alliances between high-income and low-income states result in higher levels of bilateral foreign investment.…”
Section: How Do Alliances Affect Relations Among Members?mentioning
confidence: 99%